Using a Communicative Approach to Teaching Speaking Skills at Ibrahimy University - Mislawiyadi Mislawiyadi (LP2M Universitas Ibrahimy, 2023)
This qualitative research study explores the application of the Communicative Language Teaching (CLT) approach in teaching speaking skills at University Ibrahimy. The study aims to investigate the benefits, challenges, and outcomes of implementing CLT in the context of speaking skill development. Data is collected from students and instructors through interviews and classroom observations to gain insights into their experiences and perceptions. The objectives of this research are to examine the impact of CLT on students' speaking proficiency, explore students' engagement and motivation in speaking tasks, investigate instructors' experiences and strategies in implementing CLT, and identify the role of authentic materials, cultural awareness, and feedback in enhancing students' speaking skills. The findings of this research contribute to the understanding of the practical implications of CLT in promoting speaking skills at Ibrahimy University. The outcomes are instructional practices and professional development initiatives. Adopting a student-centered approach that emphasizes authentic communication at Ibrahimy University can empower students with effective speaking skills for future academic and professional endeavors.